(untitled) (World of finance, 2019)
Introduction. Increasing the profitability of local budgets is an important issue on the way to the plundering of territorial communities, because local budgets take the main place in the socio-economic development of the territories. Particular relevance of this issue comes in terms of decentralization reform, which gives new opportunities for increasing thefinancial base of local budgets. Purpose. The purpose of the paper is to identify the peculiarities of the formation of revenues of local budgets of Ukraine in the conditions of decentralization of financial resources. Results. The theoretical questions of formation of the revenue part of local budgets are considered. The structure of the distribution of tax and non-tax revenues between the levels of the budget system of Ukraine, the role of inter-governmental transfers in the system of budget revenues of the combined terri-torial communities are investigated. The influence of decentralization reform on formation of the revenue part of local budgets is determined. Conclusions. The changes that have been made to the budget legislation in the process of decentralization reform have affected the structure of distribu-tion and source of local budgets, and strengthened the financial base of local authorities. However, it is precisely from the efforts of local self-government, the adoption of quality management decisions depends on the rational and effi-cient use of budget funds and the successful development of the community.